Estudio jurídico y doctrinario sobre la pertinencia de insertar en la legislación ecuatoriana el divorcio unilateral con la causal de daño psicológico. - López Zapata, Tania Ercilia (2023)
The present Work of Curricular Integration entitled: "Legal and doctrinal study on the relevance of inserting unilateral divorce with the cause of psychological damage into ecuadorian legislation", is a research work developed prior to obtaining the degree of Bachelor in Jurisprudence and Lawyer, in which it is analyzed that in Ecuador there exist only two traditional figures for the dissolution of the marital relationship, these being contentious divorce and divorce by mutual consent, which are provided for in the Ecuadorian Civil Code and its procedure in the General Organic Code of Processes. Having said this, the problem that is analyzed in this legal research is that both forms of divorce are inefficient according to the contemporary needs of society in matters of breach of the marriage bond, because upon studying divorce by cause it is evident that in order to propose it, at least one of the nine causes that are included in article 110 of the Civil Code must be justified. If the facts alleged are not proven, the divorce cannot proceed, and on the other hand if there is no bilateral will of the spouses to divorce, nor can the dissolution of the marital bond by mutual agreement be developed. In this sense, if our requirements do not meet the conditions of these two figures, it is not possible to effect a divorce. From here arises the need to implement a new legal figure of divorce to guarantee good family relations and the psychic integrity of the spouses, through the unilateral divorce with cause of psychological damage. This socio-legal research work was deployed based on the development of a theoretical framework and study of international regulations, and in addition, to complement the field research several methods and techniques were applied, including surveys and interviews with practicing law professionals and eighth cycle students of the Law School of the National University of Loja, the results of which were positive in favor of the new legal figure sought to propose as a third form of divorce in Ecuador. This research leads to the conclusion that it is necessary and unavoidable that the Ecuadorian civil legislation incorporate and consequently apply the legal figure of unilateral divorce with cause of psychological damage, inasmuch as it demonstrates a factual reality, so that the prosecution of the case is made in strict compliance with the rules of due process, to ensure the right to self-defense and legal certainty of the defendant.